Structural insights into the function of 23S rRNA methyltransferase RlmG (m(2)G1835) from Escherichia coli - Zhang, Heng (Cold Spring Harbor Laboratory Press, 2012)
RlmG is a specific AdoMet-dependent methyltransferase (MTase) responsible for N(2)-methylation of G1835 in 23S rRNA of Escherichia coli. Methylation of m(2)G1835 specifically enhances association of ribosomal subunits and provides a significant advantage for bacteria in osmotic and oxidative stress. Here, the crystal structure of RlmG in complex with AdoMet and its structure in solution were determined. The structure of RlmG is similar to that of the MTase RsmC, consisting of two homologous domains: the N-terminal domain (NTD) in the recognition and binding of the substrate, and the C-terminal domain (CTD) in AdoMet-binding and the catalytic process. However, there are distinct positively charged protuberances and a distribution of conserved residues contributing to the charged surface patch, especially in the NTD of RlmG for direct binding of protein-free rRNA. The RNA-binding properties of the NTD and CTD characterized by both gel electrophoresis mobility shift assays and isothermal titration calorimetry showed that NTD could bind RNA independently and RNA binding was achieved by the NTD, accomplished by a coordinating role of the CTD. The model of the RlmG-AdoMet-RNA complex suggested that RlmG may unfold its substrate RNA in the positively charged cleft between the NTD and CTD, and then G1835 disengages from its Watson-Crick pairing with C1905 and flips out to insert into the active site. Our structure and biochemical studies provide novel insights into the catalytic mechanism of G1835 methylation.